2022
DOI: 10.21037/qims-22-189
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of amide proton transfer-weighted imaging for assessing programmed death-ligand 1 status in non-small cell lung cancer: a comparative study with intravoxel incoherent motion and 18F-FDG PET

Abstract: Background: Noninvasive assessment of programmed death-ligand 1 (PD-L1) expression status in nonsmall cell lung cancer (NSCLC) is necessary. This study arm to investigate the value of 2-[ 18 F]-fluoro-2deoxy-D-glucose positron emission tomography ( 18 F-FDG PET), diffusion-weighted imaging (DWI), intravoxel incoherent motion (IVIM), and amide proton transfer-weighted imaging (APTWI) in the assessment of PD-L1 status in NSCLC.Methods: This is a prospective diagnostic study. A total of 76 patients with NSCLC und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Due to the inherent tissue heterogeneity in tumourous lesions, relying on a single parameter for a comprehensive and accurate assessment can be challenging [ 33 ]. Previous studies have highlighted the advantages of using multi-parameter combination diagnosis based on multiple quantitative or semi-quantitative parameters, particularly multiple independent predictors, in improving the diagnosis and evaluation of tumours compared with relying on single parameters [ 34 , 35 ]. Accordingly, the study employed univariate and multivariate LR analysis to identify independent predictors (SUV max , MTRasym [3.5 ppm], and ADC) for differentiating between benign and malignant SPLs among various clinical factors and quantitative and semi-quantitative parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the inherent tissue heterogeneity in tumourous lesions, relying on a single parameter for a comprehensive and accurate assessment can be challenging [ 33 ]. Previous studies have highlighted the advantages of using multi-parameter combination diagnosis based on multiple quantitative or semi-quantitative parameters, particularly multiple independent predictors, in improving the diagnosis and evaluation of tumours compared with relying on single parameters [ 34 , 35 ]. Accordingly, the study employed univariate and multivariate LR analysis to identify independent predictors (SUV max , MTRasym [3.5 ppm], and ADC) for differentiating between benign and malignant SPLs among various clinical factors and quantitative and semi-quantitative parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Meng et al. ( 48 ) conducted a prospective collection of 18 F-FDG PET/MRI image data from 76 NSCLC patients to develop a predictive model. Their findings highlighted the value of 18 F-FDG PET/MRI for the non-invasive assessment of PD-L1 status in NSCLC.…”
Section: Progress In the Application Of Pet-related Radiomics In Lung...mentioning
confidence: 99%
“…Zhou et al (47) similarly demonstrated the efficacy of 18 F-FDG-PET/CT-based radiological features in predicting TMIT-I in NSCLC, offering a promising approach for immunotherapy selection. Meng et al (48) conducted a prospective collection of 18 F-FDG PET/MRI image data from 76 NSCLC patients to develop a predictive model. Their findings highlighted the value of 18 F-FDG PET/MRI for the non-invasive assessment of PD-L1 status in NSCLC.…”
Section: Pet-related Radiomics Predicts Receptors and Molecular Tumor...mentioning
confidence: 99%
“…APT application for tumor detection and characterization was first explored and is best understood in the brain [ 12 , 13 ]. Until now, more and more APT studies have been reported in breast [ 14 , 15 , 16 ], cervix [ 17 , 18 ], prostate [ 19 , 20 , 21 ], and chest tumors [ 22 , 23 ], demonstrating its feasibility for tumor detection and characterization. However, APT weighted (APTw) imaging studies in head and neck tumors face obstacles considering motion effects such as breathing and swallowing, although the parotid glands are thought to be less influenced by such motion disturbance [ 24 ].…”
Section: Introductionmentioning
confidence: 99%